2020
DOI: 10.1177/1098612x20921056
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and pathologic characteristics of feline proteinuric kidney disease

Abstract: Objectives The aim of this study was to describe the causes, clinicopathologic features and outcomes of feline protein-losing nephropathy (proteinuria secondary to glomerular disease [PLN]). Methods Kidney biopsy/necropsy samples from proteinuric cats submitted to the International Veterinary Renal Pathology Service were retrospectively reviewed. Diagnoses based on histopathology were categorized by primary disease compartment. Clinicopathologic variables at diagnosis, development of hypoalbuminemia, anemia, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
9
1
1
Order By: Relevance
“…Several of the reports describing histopathologic changes in cats with PLN or glomerulonephritis had evidence of fibrin deposition; however, none of the studies that reported histopathology described any micro‐ or macrovascular thrombosis 84,85 . Numerous studies were considered neutral to the PECO question because they did not include a control group, they described arterial thrombosis and did not mention PLN, or they were reports focused on PLN that did not discuss or describe thrombosis 45,48,49,54,59,62,63,66–68,70,86–110 . Although these reports were considered neutral, their collective weight suggests that there is either no association or a very weak association between PLN and arterial thromboembolic complications in cats and that the overall risk of thrombosis in cats with PLN is seemingly low.…”
Section: Peco Question: Protein‐losing Nephropathy (Pln) (Cats)mentioning
confidence: 99%
“…Several of the reports describing histopathologic changes in cats with PLN or glomerulonephritis had evidence of fibrin deposition; however, none of the studies that reported histopathology described any micro‐ or macrovascular thrombosis 84,85 . Numerous studies were considered neutral to the PECO question because they did not include a control group, they described arterial thrombosis and did not mention PLN, or they were reports focused on PLN that did not discuss or describe thrombosis 45,48,49,54,59,62,63,66–68,70,86–110 . Although these reports were considered neutral, their collective weight suggests that there is either no association or a very weak association between PLN and arterial thromboembolic complications in cats and that the overall risk of thrombosis in cats with PLN is seemingly low.…”
Section: Peco Question: Protein‐losing Nephropathy (Pln) (Cats)mentioning
confidence: 99%
“…The prevalence of PLN seems to be lower in cats and, conversely to dogs, there is no evidence supporting the adoption of antithrombotic medications [8,185,187]. Although it is not licensed for use in cats and its efficacy remains unproven, acetylsalicylic acid at low doses has been encountered as antiplatelet agent in cats for the prevention of thrombosis and in particular ATE; reported dosages range widely (i.e., 5-80 mg per cat every 72 h), and special attention should be paid to the prolonged time of excretion in feline species [85,86].…”
Section: Antithrombotic Drugsmentioning
confidence: 99%
“…Serum biochemistry revealed hypoalbuminaemia (11.3 g/L; 25-45), with normal globulin (30 g/L; 25-45), hypercholesterolemia (9 mmol/L; 2.2-4), increased urea of 17.7 mmol/L (<9.9) and hyperkalaemia (5.84 mmol/L; 3.5-5.5). Creatinine was normal (89 µmol/L; 80-203) and symmetric dimethylarginine (SDMA) was normal (9 µg/dl; [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Haematology showed lymphocytosis (13.28 × 10 9 /L; 0.85-5.85).…”
Section: Case Presentationmentioning
confidence: 99%
“…1,2 Primary glomerular disease is, however, a relatively rare cause of PLN in cats. 3,4 Glomerular disease is more common in dogs, often associated with severe proteinuria. 5 There are occasional reports of immune-mediated glomerular disease in cats, with invariably poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation